Utilization of simulation by nurse educators and learner nurses at Limpopo College of Nursing Limpopo Province South Africa - Mathebula, Freedom Ntshuxeko (My University, 2017)
The aim of the study was to determine the utilization of simulation by nurse educators and learner nurses at LCN. The objectives of the study were to describe the utilization of simulation by nurse educators and learner nurses at the LCN and to develop strategies that would improve the utilization of simulation by nurse educators and learner nurses at the LCN. A qualitative research method and exploratory, descriptive and contextual research design was used with a purposive sample of fourty two participants from LCNCs. Tesch’s eight steps of qualitative data analysis were followed. The study found and concluded that there was poor utilization of simulation in clinical laboratories by both the nurse educators and learner at LCNCs. The results of the study recommends that LCNCs should have clinical laboratories managers, to be conducive in order to accommodate the number of learner nurses, to have sufficient and useful simulators, and also accessed at any time of the year by learner nurses. To employ well advanced simulators at the college through buying. Simulation sessions should be given enough time and learner nurses to be allowed to do return demonstration, and continuous practice
Thesis (M. (Nursing Science )) -- University of Limpopo, 2017
Keywords: Simulation; Utilization; Nurse Educators; Learner nurses; Nurse educators; Nursing -- Study and teaching; Nurses -- In-service training; Nursing; Nursing -- Simulation methods